Makna Pengosongan Diri Allah Trinitas dalam Perspektif Jawa: Analisis Semiotik dan Teologis atas Tokoh Semar dan Yesus Kristus - Haryadi, Dominikus Setio; Martasudjita, Emanuel Pranawa Dhatu (Societas Dei: Jurnal Agama dan Masyarakat, 2024)
Faith in the Trinity God as the foundation of Christian faith is not easily understood by most believers. It is even less easy to understand the faith in the Trinity according to a particular cultural context. This research seeks to explain the understanding of the Trinity that is interpreted in accordance with the Javanese cultural context. This research uses a literature study method with a contextual theology and pastoral circle approach. The writer takes the character of Semar in Javanese culture to deepen it in comparison with Jesus from the perspective of comparative theology. Specifically, the writer wants to look at the concept of self-emptying in Semar and also in Jesus Christ. To arrive at this research, the writer uses Charles Peirce's semiotic theory and also the thoughts of Hans Urs von Balthasar regarding the doctrine of the Trinity. The result of this research reveals the similarities between the self-emptying of Semar and Jesus Christ. However, there are clear and distinct differences between the self-emptying of Semar and that of Jesus Christ.